2003
DOI: 10.1063/1.1562009
|View full text |Cite
|
Sign up to set email alerts
|

Competition between ferroelectric and semiconductor properties in Pb(Zr0.65Ti0.35)O3 thin films deposited by sol–gel

Abstract: Asymmetric metal-ferroelectric-metal ͑MFM͒ structures were manufactured by sol-gel deposition of a lead zirconate-titanate ͑PZT with Zr/Ti ratio 65/35͒ film on Pt-coated Si, with a Au top electrode. The average remnant polarization of 9 C/cm 2 and the coercive field of 39 kV/cm were obtained from the hysteresis loop measurements. A detailed analysis of the polarization-electric field ( P -E), capacitance-voltage (C -V), and current-voltage (I -V) measurement results allowed us to estimate the near-electrode sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 40 publications
7
41
0
Order By: Relevance
“…Specifically, U 1 < U 2 results in a larger negative coercive field compared to the positive coercive field and vice versa when U 1 > U 2 . These observations are consistent with experimental observations, [38][39][40] including those by Feng et al, 41 who studied the hysteresis loops of P(VDF-TrFE) thin films with the following metal electrode configurations: Al=Al, Al=Ni, Ni=Al, and Ni=Ni.…”
Section: Effect Of Work Function Of Metal Electrodessupporting
confidence: 81%
“…Specifically, U 1 < U 2 results in a larger negative coercive field compared to the positive coercive field and vice versa when U 1 > U 2 . These observations are consistent with experimental observations, [38][39][40] including those by Feng et al, 41 who studied the hysteresis loops of P(VDF-TrFE) thin films with the following metal electrode configurations: Al=Al, Al=Ni, Ni=Al, and Ni=Ni.…”
Section: Effect Of Work Function Of Metal Electrodessupporting
confidence: 81%
“…35,36,51 We will try in the following to discuss the conditions under which the (15) and (16) can be applied and which are the limitations.…”
Section: Current-voltage (I-v) Characteristicmentioning
confidence: 99%
“…Consequently, it is considered that the conductivity mechanism is primarily interface-controlled. Boerasu et al [12] demonstrated that, for metal/film/metal structure, Pb (Zr 0.65 Ti 0.35 )O 3 thin films obey the "1/4 law", which was described using the following formula:…”
Section: Discussionmentioning
confidence: 99%